The Role of Universiti Malaysia Pahang (UMP) In Human Capital Development for The Mineral Resources Industry: Rare Earth Case Study - Zulkafli, Hassan; M. Y. M., Yunus; Nurul Ain, Ismail; A., Ramli; K., Ramesh (Penerbit Universiti Malaysia Pahang, 2017)
The demand of ‘Rare Earth Elements’ (REE) from key industries such as electronics, mobile technology, renewable energy as well as defence sectors have increased rapidly in the last decades. In fact, Malaysia is estimated to contain around 30000 metric tonnes of REE and this is a new growth area for Malaysia especially in the downstream extraction and purification processing of Heavy Rare Earth Element (HREE). Understanding this opportunity, Universiti Malaysia Pahang (UMP) has proactively took an initiative by establishing an entity which known as Rare Earth Research Centre (RERC). Moreover, in this light, UMP has also taken another critical step to particularly facing the challenge of establishing rare Earth Industry (REI) by initiating the first ever master degree in Mining and Mineral Technology (MMT). The main aim of this course is to promote a comprehensive program that supports to the activity of ‘sustainable mining’ which covering the whole spectrums of ‘cradle-to-grave’ phases. The basic idea behind this initiative is to ensure that mine operators and the stakeholders are aware about the future needs for responsible and sustainable mining industries.